1995
DOI: 10.1097/00000542-199505000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Wheezing during Induction of General Anesthesia in Patients with and without Asthma 

Abstract: This study suggests that propofol should be considered for induction of anesthesia in patients, particularly those with asthma, who require timely intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(46 citation statements)
references
References 14 publications
0
40
0
6
Order By: Relevance
“…Gold and Helrich indicated the bronchospasm seen in patients under general anesthesia as 8.1%.25 According to a study conducted by Pizov et al, [25]. 42% wheezing was determined in asthma patients in the auscultation after intubation under general anesthesia, and 6.25% wheezing in non-asthmatic ones [26]. Although our patient profile was composed of non-asthmatic healthy individuals, in our study, too, bronchospasm and wheezing incidences were found higher, like in the study of Pizov et al [26].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gold and Helrich indicated the bronchospasm seen in patients under general anesthesia as 8.1%.25 According to a study conducted by Pizov et al, [25]. 42% wheezing was determined in asthma patients in the auscultation after intubation under general anesthesia, and 6.25% wheezing in non-asthmatic ones [26]. Although our patient profile was composed of non-asthmatic healthy individuals, in our study, too, bronchospasm and wheezing incidences were found higher, like in the study of Pizov et al [26].…”
Section: Discussionmentioning
confidence: 99%
“…42% wheezing was determined in asthma patients in the auscultation after intubation under general anesthesia, and 6.25% wheezing in non-asthmatic ones [26]. Although our patient profile was composed of non-asthmatic healthy individuals, in our study, too, bronchospasm and wheezing incidences were found higher, like in the study of Pizov et al [26]. This result is most likely related to the method of data collection and to the more sensitive criteria used for establishing the diagnosis of bronchospasm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations